Heat Energy Conversion System into Electric Energy Using Peltier Technology - Dina Maizana; Lois Nikel Mahulae; Mhd Nurul (Faculty of Engineering, Malikussaleh University, 2024)
This paper explains about to design and test a system for converting heat energy into electrical energy using a Peltier thermoelectric module. The Peltier module utilizes the temperature difference between the hot and cold sides to generate electricity through the Seebeck effect. The use of this technology is relevant in efforts to utilize renewable energy, especially in utilizing waste heat from engines or other unused heat sources. The designed system consists of a Peltier module, heat source, and supporting electronic circuits to optimize energy conversion. Tests are carried out at various temperature levels to measure the voltage and electrical power produced. The research results show that the system is capable of producing electrical power of up to several watts. Factors that influence system performance, such as temperature differences and module quality, are analyzed to provide suggestions for further development. This research shows the potential application of Peltier modules in small-scale thermal energy utilization systems, although increased efficiency and design optimization are needed for wider use.